2021
DOI: 10.3389/fnagi.2021.736937
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Amyloid-β and Neuropsychological Performance in Patients With Cognitive Decline

Abstract: Objective: To investigate the association between plasma amyloid-β (Aβ) levels and neuropsychological performance in patients with cognitive decline using a highly sensitive nano-biosensing platform.Methods: We prospectively recruited 44 patients with cognitive decline who underwent plasma Aβ analysis, amyloid positron emission tomography (PET) scanning, and detailed neuropsychological tests. Patients were classified into a normal control (NC, n = 25) or Alzheimer’s disease (AD, n = 19) group based on amyloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…Several studies indicate the potential for the plasma levels of different amyloid-β (Aβ) variants to function as AD biomarkers, due to their accuracy and predictivity [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. This is not surprising considering that CSF Aβ peptides represent one of the core biomarkers in AD diagnosis, and that, at the same time, there is an urgent need to identify more accessible ones [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies indicate the potential for the plasma levels of different amyloid-β (Aβ) variants to function as AD biomarkers, due to their accuracy and predictivity [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. This is not surprising considering that CSF Aβ peptides represent one of the core biomarkers in AD diagnosis, and that, at the same time, there is an urgent need to identify more accessible ones [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The significant association between obese-BMI and plasma Aβ42/40 ratio were persistently observed after adjusting the data to age, age-squared and sex, whilst Aβ40 and Aβ42 did not show any independent significant differences between lean, overweight and obese groups. The low plasma Aβ42/40 ratio observed amongst the obese BMI group coincides with a greater risk of AD, as lower plasma Aβ42/40 ratio is consistently associated with high cerebral amyloid burden, greater cognitive deterioration and increased risk of developing AD [8][9][10][11][12][13][14][15][20][21][22][23]. Therefore, our data collectively suggest that obesity and higher BMI may implicate a higher risk of AD through disturbances in plasma Aβ homeostasis.…”
Section: Discussionmentioning
confidence: 69%
“…Many studies have evaluated plasma levels of Aβ40 and Aβ42 as predictors of AD or cognitive decline [7]. Recent findings show that the dyshomeostasis of plasma Aβ, particularly low plasma Aβ42/40 ratio can predict the risk of AD at an accuracy of ~90% [8][9][10][11][12][13][14][15]. However, few studies to date have investigated the association between obesity and plasma Aβ homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Amyloid β is proposed to induce hyperphosphorylation of tau protein during the pathological severity of dementia ( Mocanu et al, 2008 ; Fan et al, 2020 ). Studies in the elderly population have found that amyloid β is related to neuropathological performance ( Yun et al, 2021 ; Zecca et al, 2021 ). The neuroprotective effects of coenzyme Q10 have also been demonstrated in cells and animal models ( Elipenahli et al, 2012 ; Komaki et al, 2019 ; Ekicier Acar et al, 2020 ; Ibrahim Fouad, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of coenzyme Q10 could attenuate amyloid β accumulation and mitigate Alzheimer’s-like behavioral and pathological symptoms ( Yang et al, 2008 ; Muthukumaran et al, 2018 ; Ibrahim Fouad, 2020 ). Recent published data showed that lower levels of amyloid β-42 and amyloid β-42/40 ratio was found in dementia patients ( Hanon et al, 2022 ; Thijssen et al, 2022 ), but other researchers found that patients with dementia had higher levels of amyloid β-42, and the level of plasma amyloid β-42/40 ratio was correlated with amyloid positivity in the bilateral frontal, parietal, temporal, and occipital cortices ( Manafikhi et al, 2021 ; Yun et al, 2021 ). The levels of amyloid β-42 and β-40 in dementia patients appear to remain uncertain.…”
Section: Discussionmentioning
confidence: 99%